2021
DOI: 10.1101/2021.05.11.443507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid analysis of strigolactone receptor activity in aNicotiana benthamiana dwarf14mutant

Abstract: DWARF14 (D14) is an ɑ/β-hydrolase and receptor for the plant hormone strigolactone (SL) in angiosperms. Upon SL perception, D14 works with MORE AXILLARY GROWTH2 (MAX2) to trigger polyubiquitination and degradation of DWARF53(D53)-type proteins in the SUPPRESSOR OF MAX2 1-LIKE (SMXL) family. We used CRISPR-Cas9 to generate knockout alleles of the two homoeologous D14 genes in the Nicotiana benthamiana genome. The Nbd14a,b double mutant had several phenotypes that are consistent with the loss of SL perception in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…S6 A ). To determine whether the remaining rac -GR24 response was mediated by D14 or KAI2, we also performed the experiment in an Nbd14a,b double mutant that has loss-of-function mutations in the two D14 homoeologs in N. benthamiana ( 61 ). We found that the SMAX1 reporter was not degraded in response to KAR 1 , KAR 2 , or rac -GR24 in Nbd14a,b leaves when KUF1 was overexpressed ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S6 A ). To determine whether the remaining rac -GR24 response was mediated by D14 or KAI2, we also performed the experiment in an Nbd14a,b double mutant that has loss-of-function mutations in the two D14 homoeologs in N. benthamiana ( 61 ). We found that the SMAX1 reporter was not degraded in response to KAR 1 , KAR 2 , or rac -GR24 in Nbd14a,b leaves when KUF1 was overexpressed ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins are specifically targeted by D14 and not by KAI2 (Wang et al 2015;Khosla et al 2020a;White et al 2022). Finally, SMXL3-and aSMXL4-clade proteins, represented by SMXL3, SMXL4, and SMXL5 in Arabidopsis, regulate phloem development and anthocyanin abundance (Cho et al 2018;Wallner et al 2017Wallner et al , 2023Wu et al 2017;Li et al 2024).…”
Section: Introductionmentioning
confidence: 99%